Experimental Simulation of Natural Heat Convection from Finned Vertical Plate with Different Inclinations - Shehab, Saad Najeeb (Al-Khwarizmi Engineering Journal, 2017)
In this work an experimental simulation is made to predict the performance of steady-state natural heat convection along heated finned vertical base plate to ambient air with different inclination angles and configurations of fin array. Two types of fin arrays namely vertical fins array and V-fins array on heated vertical base plate are used with different heights and spaces. The influence of inclination angle of the plate , configuration of fins array and fin geometrical parameters such as fin height and fin spacing on the temperature distribution, base convection heat transfer coefficient and average Nusselt number have been plotted and discussed. The experimental data are correlated to a formula between average Nusselt number versus Rayleigh number for vertical plate and vertical fins array. The results indicate that the configuration of V-fins array gave best natural-convection heat transfer performance as base heat transfer coefficient about 20% greater compared with vertical fins array. Experimental simulation data and correlations of the present work are compared with a previous works shows good agreement.